The missing piece in the DSA puzzle? Article 18 of the EMFA and the media privilege - Matteo Monti (Rivista Italiana di Informatica e Diritto)
This article examines the provisions of Articles 18 and 19 of the European Media Freedom Act (EMFA) in relation to the digital governance framework established by the Digital Services Act (DSA), with a particular focus on the media privilege codified in Article 18 of the EMFA. Section 2 analyses the media privilege of Articles 18 and 19 of the EMFA from three perspectives: the requirements for obtaining this privilege and the media entities eligible for it; the functioning of the privilege and its intersections with the DSA provisions; and the transparency in its application, including the role of the Board under Article 19 of the EMFA. Section 3 explores the regulatory framework governing the media privilege in Article 18 of the EMFA and addresses criticisms of this online media privilege. More specifically, it focuses on two main criticisms: the risk of granting this privilege to agents of disinformation and the “constitutional” legitimacy of the privilege. The final remarks summarise the main considerations of the different sections and offer concluding observations.